2018
DOI: 10.4172/clinical-practice.1000393
|View full text |Cite
|
Sign up to set email alerts
|

Quantum biophysics of water

Abstract: A large database of 1773 HCC patients in Turkey was examined. 41.9% had alpha-fetoprotein (AFP) levels <20 IU/ml and an additional 16.123% had values between 20-100 IU/ml. This 58% of the cohort (<100 IU/ml AFP levels) was examined in detail. 66% of patients with small (<5 cm) HCCs had low AFP, compared to 49% of patients with larger (>5 cm) HCCs. The mean diameter (MTD) of larger MTD, low AFP tumors was 8.4cm. Therefore, factors other than AFP must contribute to HCC tumor growth. Larger tumors in low AFP pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
(42 reference statements)
0
15
0
Order By: Relevance
“… 7 Though AFP is the gold-standard serum marker for HCC, the utility of AFP for surveillance is limited by its low sensitivity and specificity. 8 A large proportion of HCC patients (42%) in fact do not have elevated levels of AFP (>20 IU/mL), 9 emphasizing the urgent need to develop better biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Though AFP is the gold-standard serum marker for HCC, the utility of AFP for surveillance is limited by its low sensitivity and specificity. 8 A large proportion of HCC patients (42%) in fact do not have elevated levels of AFP (>20 IU/mL), 9 emphasizing the urgent need to develop better biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that GGT values represent a useful discriminant for HCC tumor aggressiveness in a large percentage of untransplantable HCC patients who have low AFP values[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers are also, often, of only limited help. Alpha fetoprotein (AFP) levels are not elevated in a significant proportion of patients with HCC 13,14. CA19-9 is usually elevated in patients with cholangiocarcinoma but may be falsely elevated in certain situations (e.g., cholangitis, biliary obstruction, smokers, etc.).…”
Section: Discussionmentioning
confidence: 99%